Special Education: Clinical Application of Chinese Version Sensory Profile (Asian Education Studies, 2016)
Chinese Version Sensory Profile (Cheung & Siu, 2009) is a validated tool for healthcare professionals to analyse the impact on how sensory impairment may affect children in carrying out daily activities. In this study, a total of 15 caregivers were recruited from a special school for mental handicap in Hong Kong to complete a survey in respect of the children’s condition (11 males and 4 females aged 6 to 15 years old). Results showed that the proportion falling on imbalance and dysfunction category was highest in visual processing (66.6%) and lowest in emotional/social responses (26.6%). In order for children with sensory impairments to engage in daily life and learning through the process, a series of activities are recommended to parents and teachers.